Implementasi Manajemen Kurikulum Pada Pendidikan Anak Usia Dini Yayasan Pendidikan Islam TK Makmur Al Ihsan Desa Penuguan Kecamatan Selat Penuguan Kabupaten Banyuasin - Darmawati Darmawati; Al Hadi Yan Putra; Nuril Furqan (Departement of Mathematics Education, 2023)
This study aims to find out how the implementation of curriculum management in early childhood education Islamic Education Foundation Makmur Al Ihsan Kindergarten, Penuguan Village, Penuguan Strait District, Banyuasin Regency. This research is a qualitative research with a case study method. This research was conducted at the Makmur Al Ihsan Kindergarten Islamic Education Foundation, Penuguan Village, Penuguan Strait District, Banyuasin Regency with human resources consisting of 6 people including the principal, curriculum representative, operator, treasurer and two teachers who teach in class zero small A and class zero small B. Data collection techniques using interviews, observation and documentation. Test the validity of the data using trustworthiness (triangulation), transferability and dependability. The results of this study indicate that: (1). The curriculum planning for the Makmur Al Ihsan Kindergarten Islamic Education Foundation has been carried out in accordance with the standard implementation process that applies to the Makmur Al Ihsan Kindergarten Islamic Education Foundation by implementing an independent curriculum with the aim of conforming to the goals of education in Indonesia. (2) The implementation of curriculum management for the Makmur Al Ihsan Kindergarten Islamic Education Foundation is delivered in accordance with the lesson schedule that has been prepared by the school. (3) Organizing in the curriculum management of the Makmur Al Ihsan Kindergarten Islamic Education Foundation is designed using the curriculum that has been implemented. (4) Monitoring and evaluating the curriculum management of the TK Makmur Al Ihsan Islamic Education Foundation, there are several processes such as observation, anecdote notes, conversations, assignments and performance of work.